Evaluation of Treated Wastewater Quality for Reuse in the Northern Region of Minas Gerais - Peres, Camilla Silva; Ladeia, Mônica Maria; Da Silva, Julia Ferreira; Dias, Laís Pereira; Lopes, Ludmila Ferreira (RGSA : Revista de Gestão Social e Ambiental, 2024)
Objective: This study aims to analyze the quality of effluents treated at three Wastewater Treatment Plants (WWTPs) in the northern region of Minas Gerais, evaluating reuse potential and proposals.